2010
DOI: 10.1149/1.3291976
|View full text |Cite
|
Sign up to set email alerts
|

Low Cost, Environmentally Benign Binders for Lithium-Ion Batteries

Abstract: The stringent environmental requirements regarding the mobility energy usage are forcing most automakers to develop hybrid electric vehicles, which allows for a more efficient and thus less polluting use of fossil combustibles. A vast deployment of such vehicles involves producing and recycling of batteries on the thousand tons per year scale. Present Li-ion technologies involve the use of fluorinated binders, which are costly, and the use of environmentally unfriendly volatile organic compounds for the proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
213
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(227 citation statements)
references
References 26 publications
5
213
0
Order By: Relevance
“…Even though they were still insoluble in water, Maleki et al [13] and Du Pasquier et al [11] showed that reduced heat was obtained when poly(phenol-formaldehyde), poly(vinylchloride) or poly(acrylonitrile) were used as binders. (2) Another disadvantage of using PVDF is its price which is about US$ 20 per kg in North America (D 15-18 per kg in Europe [19] it is a known mutagen, tumorigen and reproductive effector; its LD 50 on skin rabbit is 8 mg kg −1 . (4) In addition, as mentioned by Lux et al it is not easy to dispose PVDF at the end of the battery life [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though they were still insoluble in water, Maleki et al [13] and Du Pasquier et al [11] showed that reduced heat was obtained when poly(phenol-formaldehyde), poly(vinylchloride) or poly(acrylonitrile) were used as binders. (2) Another disadvantage of using PVDF is its price which is about US$ 20 per kg in North America (D 15-18 per kg in Europe [19] it is a known mutagen, tumorigen and reproductive effector; its LD 50 on skin rabbit is 8 mg kg −1 . (4) In addition, as mentioned by Lux et al it is not easy to dispose PVDF at the end of the battery life [19].…”
Section: Introductionmentioning
confidence: 99%
“…(2) Another disadvantage of using PVDF is its price which is about US$ 20 per kg in North America (D 15-18 per kg in Europe [19] it is a known mutagen, tumorigen and reproductive effector; its LD 50 on skin rabbit is 8 mg kg −1 . (4) In addition, as mentioned by Lux et al it is not easy to dispose PVDF at the end of the battery life [19]. Thus binders with decomposition products that are more environmentally friendly are needed for preparing electrodes materials for Li-ion batteries.…”
Section: Introductionmentioning
confidence: 99%
“…9 Most of these studies were performed with the commercially available binder, polyvinylidene fluoride (PVDF), which is widely used in Li-ion batteries because of its electrochemical stability at the high voltage range. In recent years, new binder development includes (1) seeking new electronically conductive binders with high elasticity in order to accommodate the large volume change of AMs during insertion and extraction of lithium-ions, 7,[10][11][12][13][14][15][16][17] (2) replacing the costly, environmentally unfriendly, and volatile organic solvent used in the manufacturing of electrode, [18][19][20] and (3) increasing the adhesion strength between the binder and other components of electrode (AMs and conductive materials in general). 5,[21][22][23][24][25][26] However, the development of binders is hindered by the lack of standard tests of binder adhesion properties and a fundamental understanding of adhesion mechanism.…”
mentioning
confidence: 99%
“…PVdF may have superior chemical and electrochemical stability, but this does not entirely eliminate Li-ion battery producers' problems such as having to use toxic organic solvents such as N-methylpyrrolidone (NMP), which are indispensable for dissolving polymer. In addition, the cost of PVdF-based electrodes is still a concern in the battery industry [4][5][6][7][8]. What is more, PVdF also tends to swell in organic solvents, which can lead to the active mass breaking away from the electrode current collector during battery work [1].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a large amount of effort has been put into the creation of an environment-friendly and cost-effective binder for lithiumion batteries. Extensive research has been conducted into in this field, such as carboxymethyl cellulose (CMC), mainly as its sodium neutralized derivative, and polyacrylic acid (PAAH) [8][9][10][11]. Recently, some new kinds of binders have been tested for lithium-ion batteries, for example acrylate polymers, such as polyacrylic acid (PAA) containing carboxyl groups maintain excellent cyclic retention for C-Si-based electrode materials thanks to hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%